Screening of mutations and polymorphisms in the glucokinase gene in Czech diabetic and healthy control populations - Lukášová, P; Včelák, J; Vaňková, M; Vejražková, D; Andělová, K; Bendlová, B (Physiological research, 2008)
Glucokinase (GCK) plays a key role in glucose metabolism. GCK mutations are known as a pathogenic cause of maturity-onset diabetes of the young type 2 (MODY2). These mutations are also found in gestational diabetics. The aim of our study was to assess the variability of the GCK gene in the Czech diabetic and control populations. We screened all 10 exons specific for the pancreatic isoform of glucokinase (1a and 2-10) including the intron flanking regions in 722 subjects (in 12 patients with an unrecognised type of MODY and their 10 family members, 313 patients with diabetes mellitus type 2 (DM2), 141 gestational diabetics (GDM), 130 healthy offspring of diabetic parents, and 116 healthy controls without family history of DM2). In two MODY families we identified two mutations in exon 2 of the GCK gene: a novel mutation Val33Ala and the previously described mutation Glu40Lys. In other subgroups (excluding MODY families) we detected only intronic variants and previously described polymorphisms in exons 6 (Tyr215Tyr) and 7 (Ser263Ser), we did not find any known GCK pathogenic mutation. We observed no difference in the frequencies of GCK polymorphisms between Czech diabetic (DM2, GDM) and non-diabetic populations.
Keywords: exony; Genetic Testing; glukokinasa; Male; mutace; genetická variace; polymorfismus genetický; genetické testování; Česká republika; Exons; Glucokinase; Pregnancy; těhotenství; Adult; Aged; dospělí; Diabetes Mellitus, Type 2; mužské pohlaví; senioři; Polymorphism, Single-Stranded Conformational; Polymorphism, Genetic; diabetes mellitus 2. typu; Introns; Czech Republic; polymorfismus konformace jednovláknové DNA; Diabetes, Gestational; introny; lidé; gestační diabetes; ženské pohlaví; Humans; Mutation; Genetic Variation; Female; lidé středního věku; Middle Aged